Obtaining target protein fractions from marine organisms of Antarctic Region - D. Gladun; T. Vovk; N. Raksha; O. Savchuk; L. Ostapchenko (Ukrainian Antarctic Journal, 2014)
Antarctic region has a great diversity of species, among them there are representatives that outline practical for Biotechnology some interest from the point of view of production of biologically active substances with the possibility of their further use for the creation of pharmaceuticals. Animal tissue Antarctic region have a wide range of proteins and peptides. The molecules of protein nature, having mechanisms directed action, that is, the enzymes of different specificity - are of particular interest to researchers. In this paper describes the development and application of methodological approaches for further work and to protein molecules and peptides tissues of marine aquatic Antarctic region.